2-(4-Isopropylbenzylidene)propanoic acid - Muhammad, Niaz (International Union of Crystallography, 2008)
The two molecules in the asymmetric unit of the title compound, C(13)H(16)O(2), form dimers through O—H⋯O hydrogen bonding, resulting in R (2) (2)(8) rings. Each carboxyl O atom is involved in interamolecular C—H⋯O hydrogen bonds, forming five-membered rings. There exist dissimilar dihedral angles within the two molecules, for example the carboxylate and isopropyl groups make dihedral angles of 59.6 (4) and 71.7 (3)° in the two molecules. There are no intermolecular π interactions.